DNA methylation and complex human disease - Neidhart, Michel (Amsterdam : Elsevier, 2016)
DNA Methylation and Complex Human Disease reviews the possibilities of methyl-group-based epigenetic biomarkers of major diseases, tailored epigenetic therapies, and the future uses of high-throughput methylome technologies. This volume includes many pertinent advances in disease-bearing research, including obesity, type II diabetes, schizophrenia, and autoimmunity. DNA methylation is also discussed as a plasma and serum test for non-invasive screening, diagnostic and prognostic tests, as compared to biopsy-driven gene expression analysis, factors which have led to the use of DNA methylati.
''4.5.3 Viral Infections''''4.6 Maternal Mood and Experience in Early Life'';''4.7 Physical Exercise'';''4.8 Conclusion'';''References'';''5 DNA Methylation and Epidemiology'';''5.1 Introduction'';''5.2 Endocrine Disrupting Chemicals'';''5.2.1 Bisphenol-A'';''5.2.2 Diethylstillbestrol'';''5.2.3 Cadmium'';''5.3 Epigenomics and Breast Cancer'';''5.3.1 RASSF1A'';''5.3.2 P16/CDKN2A'';''5.4 Tobacco Smoking'';''5.4.1 F2RL3, Smoking, and Cardiovascular Diseases'';''5.4.2 RUNX3, Smoking, Low Birth Weight, and Lung Carcinomas'';''5.4.3 AHRR, Smoking, and Lung Metastasis''
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed August 20, 2015)
Elsevier
Keywords: DNA -- Methylation; Medical genetics; SCIENCE / Life Sciences / Biochemistry; DNA -- Methylation; Medical genetics; DNA -- Methylation; Epigenesis, Genetic; Medical genetics; Electronic books; Electronic books